Aspectos ecológicos e sociais da coleta informal de resíduos sólidos urbanos do município de São Carlos - SP - Rancura, Sheila Aparecida de Oliveira (2005)
This work was developed along with informal waste collectors of recyclable solid waste in the urban area of the city of São Carlos SP. An effort has been performed with the aim of combining ecological studies with the garbage problematic and social exclusion the informal waste collection brings. The adequacy of concepts of the ecological theory (ecological niche, foraging models) to the case of the waste collectors studied allowed placing the role of individuals in the ecosystem and inferring on the resource utilization forms and their implications for the environment. The methodological procedures used combined direct observations and free interviews with structured questionnaires (socioeconomic and informal collection production data). Most informal waste collectors (80%) present generalist collection strategy, also presenting, however, high dependence degree on some types of waste such as aluminum, paper and ferrous materials. The behavior of the informal waste collectors is similar to behavior predicted for foragers by the optimal foraging theory. The contribution of the informal collection for recycling market is of order of 97.3 kg/day/collector, being hidden by its stealth situation and the gains they profit are found at minimum levels as possible in order to allow they subsistence. One of the effects of this activity on the environment is its performance as negative feedback on one component the garbage which causes environmental deterioration. One believes that the recognition of the collection social and environmental importance and its removal from informality are the first step to change the stealth situation that informal waste collectors are submitted to.